Seizure severity is associated with poor quality of life in people living with epilepsy (PLWE) in Uganda: A cross-sectional study - Kaddumukasa, Mark (Epilepsy Behav, 2019)
RATIONALE: There is a paucity of information about the association of seizure severity and quality of life in people living with epilepsy (PLWE) in sub-Saharan Africa. We evaluated the relationship between seizure severity and health-related quality of life of patients with epilepsy being followed up in an outpatient neurology clinic in urban central Uganda METHODS: Forty-eight PLWE who met the study inclusion criteria were enrolled. The study questionnaire was comprised of the Chalfont Seizure Severity Scale, and the Quality of Life Inventory in Epilepsy (QOLIE-31). Spearman’s rank correlation coefficient was used to determine the association between seizure severity and quality of life score. RESULTS: The median age of the study participants was 25 years, with median age (IQR) of epilepsy onset of 12 (6−18) years. Over 57.4% of the study participants were unemployed. The mean (SD) of QOLIE-31 and Seizure Severity Score was 62.5 (14.5) and 62.4 (1. 6), respectively. There was no gender difference in the seizure severity scores (P = 0. 451). An inverse relationship existed between seizure severity and the total QOLIE-31 score (Spearman’s rank correlation coefficient, r = −0.48, p = 0.001), and seizure worry (r = −0.31, p=0.030), CONCLUSIONS: In this Ugandan sample seizure severity is unacceptably high, and directly impacts the life of PLWE. Interventions that reduce seizure severity are urgently needed in our settings to reduce seizures and improve the quality of life in PLWE.